2019
DOI: 10.1002/smll.201902974
|View full text |Cite
|
Sign up to set email alerts
|

Ultrabroad Band Microwave Absorption of Carbonized Waxberry with Hierarchical Structure

Abstract: Developing microwave absorption materials with broadband and lightweight characters is of great significance. However, it is still a great challenge for carbonized biomass without loading magnetic particles to cover the broad microwave frequency. Herein, it is proposed to carbonize freeze‐dried waxberry to make full use of its natural hierarchical gradient structure to target the ultrabroad band microwave absorption. The carbonized freeze‐dried waxberry shows radial‐gradient and hierarchical structure. The dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
79
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 194 publications
(80 citation statements)
references
References 45 publications
1
79
0
Order By: Relevance
“…[ 11–16 ] In particular, the latest reports have showed that hierarchical 3D structures containing 1D or 2D cells exhibit exciting MA properties. [ 17–22 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 11–16 ] In particular, the latest reports have showed that hierarchical 3D structures containing 1D or 2D cells exhibit exciting MA properties. [ 17–22 ]…”
Section: Introductionmentioning
confidence: 99%
“…According to Maxwell's theory, excessive conductive loss might lead to impedance mismatch, causing an increase in the microwave reflection rather than absorption. [16,17] Wang et al showed that the RL of pure graphene is no less than −5 dB over the entire testing frequency (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18), which is far from the requirement of practical applications. [18] In addition, researchers have found that pure graphene could only provide short-term protection for the metal substrate.…”
Section: Introductionmentioning
confidence: 99%
“…10d, f), which rendered these Co/C composites as multi-functional materials with great potential in plenty of practical applications. Biomass materials are also common three-dimensional scaffolds in virtue of their biological structure [150,151]. Wheat flour and cotton fiber were utilized as biomass hard templates to combine with Co/C polyhedrons derived from ZIF-67 crystals [152,153], and both of them could promise effective improvements in EM absorption, and especially for nanoparticles and then incubated Fe 3 O 4 /ZIF-67@WA with the help of 2-methylimidazole and finally converted Fe 3 O 4 /ZIF-67@WA into hierarchical composite (FeCo/C@ WC) with tomato-like polystage micro-nanoarchitecture (Fig.…”
Section: Template-mediated Assemblymentioning
confidence: 99%